Asymptomatic renal thoracic ectopia, pulmonary hypoplasia, and Bochdalek hernia. Issue 8 (August 1990) - Hulks, G; Cowan, M D; Kerr, J W
Abstract : Right sided intrathoracic kidney associated with ipsilateral pulmonary hypoplasia and Bochdalek hernia in a 13 year old girl was diagnosed by computed tomography.